Convergence of EMU Equity Portfolios - Maela Giofre (FIW - Research Centre International Economics, 2009)
This paper demonstrates that, after integration, equity portfolios of countries that joined the European Monetary Union have converged at faster rate than those of NON EMU countries. This outcome can be interpreted as a combination of the convergence of inflation rates and the convergence of investment barriers. On the one hand, the common monetary policy might have driven a stronger comovement in inflation rates, leading to increasingly similar hedging strategies among member countries. On the other hand, exposure to the common currency might have homogenized bilateral investment barriers, thus inducing increasingly similar portfolio allocations among member countries. We find that the comovement of inflation rates has not significantly increased after EMU inception, pointing toward an exclusive role for convergence in investment barriers.
Keywords: F21; F30; F36; G11; G15; 330; financial integration; EMU; inflation hedging; investment barriers